Implementasi Pelimpahan Kewenangan Bupati Kepada Camat Untuk Meningkatkan Pelayanan Publik Dalam Perspektif Reformasi Administrasi Publik (Studi di Kecamatan Mojoanyar Kabupaten Mojokerto) - Agil, Pendit Pranasworo (Jurnal Administrasi Publik, 2015)
Abstract: Delegation of Authority Implementation Regents To Subdistrict To Improve Public Services Public Administration Reformin Perspective (Studies In District Mojoanyar District, Mojokerto). Mojokerto local governments continue to strive for a balance between the tasks with the delegation of authority from there gents to the sub-district headsMojoanyar village. One of the newlaws passed by the Government of MojokertoMojokerto Regency Regulation No.9 of 2008 on government affairs under the authority of the Government of Mojokerto regency. The purpose of this study is to describe the implementation of delegation of authority to the sub-district heads regent to improve public services in the perspective of public administration reformand to determine the factors supporting and inhibiting the implementation of delegation of authority to the district head Mojoanyar regent of Mojokerto regency. The result of this research is the process of delegation of authority to the district head Mojoanyar Regentin theÂ  form of services in the field of election administration by village officials, economic and development authority to carry out the management camats Building Permit(IMB), in education and health sub-district head authorizing the establishment of the school authorities services and family planning program(KB), in the field of personnel authorized to give permission camat leave for Civil Servants(PNS), set notification of scheduled salary increases for civil servants.The result of this research is the process of delegation of authorityto the district head Mojoanyar Regentin the form of services in the field of election administration by village officials, economic and development authority to carry out the management camats Building Permit(IMB), in education and health sub-district head authorizing the establishment of the school authorities services and family planning program(KB), in the field of personnel authorized to give permission camat leave for Civil Servants(PNS), set notification of scheduled salary increasesÂ  for civil servants. Keywords: delegation of authorityto the district head Mojoanyar Regent Mojokerto, an implementation of the sub-district transfer of Regents Mojoanyar Abstrak: Implementasi pelimpahan kewenangan Bupati kepada Camat untuk meningkatkan Pelayanan publik dalam Perspektif Reformasi Administrasi Publik (Studi di Kecamatan Mojoanyar Kabupaten Mojokerto). Pemerintah dareah kabupaten Mojokerto terus mengupayakan agar keseimbangan antara tugas dan pelimpahan wewenangdari bupati kepada camat desa Mojoanyar. Salah satu produk hukum terbaru yang disahkan oleh Pemerintah Kabupaten Mojokerto No. 9 Tahun 2008 tentang urusan pemerintahan yang menjadi kewenangan Pemerintah Daerah Kabupaten Mojokerto. Tujuan dari penelitian ini adalah untuk mendeskripsikan implementasi pelimpahan kewenangan bupati kepada camat untuk meningkatkan pelayanan publik dalam perspektif reformasi administrasi publik dan untuk mengetahui faktor-faktor yang menjadi pendukung dan penghambat implementasi pelimpahan kewenangan Bupati kepada Camat mojoanyar Kabupaten Mojokerto. Hasil penelitian ini adalah proses pelimpahan kewenangan Bupati kepada Camat Mojoanyar dalam bentuk pelayanan di bidang pemerintahan dengan melakukan pemilihan perangkat desa, bidang ekonomi dan pembangunan camat berwenang melakukan pengurusan Surat Ijin Mendirikan Bangunan (IMB), di bidang pendidikan dan kesehatan camat berwenang memberi ijin pendirian sekolah dan pelayanan program Keluarga Berencana (KB), di bidang kepegawaian camat berwenang memberikan ijin cuti bagi Pegawai Negeri Sipil (PNS), menetapkan pemberitahuan kenaikan gaji berkala bagi PNS. Kata kunci: pelimpahan wewenang Bupati kepada Camat Mojoanyar Kabupaten Mojokerto, bentuk implementasi pelimpahan Bupati kepada Camat Mojoanyar